Institutionalizing the revolutionary movement: a study in the transformations of the Egyptian public sphere - Abu-Zaid, Reem (AUC Knowledge Fountain, 2012)
This research focuses on the Egyptian Social Democratic Party (ESDP) and the Egyptian Stream Party (ESP) as case studies to understand how post-January 2011 political parties approached mainstream politics, and how the revolutionary protest movements developed to further penetrate the public sphere of Egyptian politics. The focal concern of this research is to investigate how these political parties were formed in the aftermath of popular participated uprising, and what characteristics they inherited from a long heritage of informal activism to mainstream politics.